PERAN TEKNOLOGI DALAM MENINGKATKAN EFEKTIVITAS AUDIT INTERNAL - Salihi, Said Saleh (JITAA : Journal Of International Taxation, Accounting And Auditing, 2024)
Internal audit plays a crucial role in ensuring compliance, operational efficiency, and risk mitigation within an organization. With the advancement of technology, internal audit has undergone significant transformation in terms of effectiveness and efficiency. In today's digital age, technologies such as artificial intelligence (AI), big data analytics, robotic process automation (RPA), and blockchain technology have had a major impact on internal audit effectiveness. This study aims to analyze the role of technology in enhancing the effectiveness of internal audits, focusing on the implementation of big data, artificial intelligence (AI), and technology-based audit management systems. The research method used is a literature review and secondary data analysis. The findings indicate that the use of technology in internal audits can improve accuracy, efficiency, and anomaly detection more rapidly than traditional methods. The conclusion of this study emphasizes the importance of technological adaptation in internal auditing to enhance supervision and control quality within organizations.